The essence of the crime perpetrator mercenary offenses: theoretical aspect - Atakhanova G.M. (Хабаршы. Заң сериясы, 2016)
This article describes the General characteristics of the personality of the offender and corrupt the structure of the personality of the perpetrator: value orientations and aspirations of the individual, their social position and relationships, interests, needs and habits. Also investigated psychological concepts of criminal essence of personality of the offender and to formulate complex scientificpractical recommendations for improving enforcement and remedies to combat crime involving criminal law measures, forecasting and prevention of criminal acts, the correction of convicted persons.